Sulfamethoxazole removal in membrane-photocatalytic reactor system – experimentation and modelling. Issue 13 (7th June 2019) - Asha, Raju C.; Yadav, M. S. Priyanka; Kumar, Mathava
ABSTRACT: In this study, the efficacy of membrane-photocatalytic reactor (MPR) in sulfamethoxazole (SMX) removal was explored at a fixed initial SMX concentration, i.e. 100 mg/L. A supported catalyst, i.e. TiO2 on granular activated carbon (GAC–TiO2 ), was used for MPR experiments. The SMX removal efficiency of the MPR was investigated under a range of hydraulic retention time (i.e. HRT from 51 to 152.5 min) and TiO2 catalyst dosage (55–50 mg/L). A maximum SMX removal efficiency of 83.6% was observed under 220 mg/L catalyst dosage and 80 min HRT. The increase in catalyst dosage from 55 to 550 mg/L has increased the transmembrane pressure of the reactor from 9.8 to 22.2 kPa. A multiple non-linear regression model was developed based on the experimental data and its significance was analyzed using two-way ANOVA. Based on the model, the optimal HRT and catalyst dosage for complete SMX removal (100%) were found out. The comparison of photocatalytic degradation experiments with sorption experiments conducted earlier revealed that SMX removal in the MPR was mainly by photocatalytic degradation and not by adsorption onto GAC–TiO2 catalyst. However, the performance of MPR in removing other emerging pollutants from real-time wastewaters could be explored before its field-scale application.